Critical evaluation of Employee Involvement at DHL Aviation (UK) Ltd., East Midlands, Nottinghamshire - Nagy, Juliet Georgina (2012)
Purpose – Employee engagement has become an increasingly popular refrain amongst HR scholars and consulting firms. Nonetheless, although studies suggest employee engagement improves organisational performance, it has also been argued that the topic has not been researched sufficiently. There remain gaps in knowledge within the academic literature about clarity of definitions and true evidence of positive outcomes. The purpose of this study is to investigate employee engagement within DHL, a global firm –– who pride themselves on their employees, and spend considerable resources to measure and improve employee engagement – in order to determine what employee engagement wishes to achieve and whether this comes to fruition. Design/methodology/approach – Using a case study, an initial online survey was completed by 150 employees working in a variety of departments, jobs and levels within DHL at EMA. The majority of participants were aged between 40-49, 83% were of white British origin and 74% were male. Participants had been working for the organisation for an average of 5-10 years. The survey was based on employment engagement questions from the management consultancy firm, Gallup, and included measures of job satisfaction and organisational engagement. Subsequent one-to-one semi-structured interviews took place with 12 participants, from both managerial level and lower-level, based on their answers given to the survey. These answers were compared to 2011 DHL opinion survey results and secondary documents. A reflective journal was used to clearly document findings and as a learning tool to aid the research process. Findings – Results from the initial survey indicate that an average 24% gave the highest points about employee engagement at DHL and an average 11% gave the lowest points. Consequently, two areas arose that require additional observation: receiving recognition or praise for good work, and the importance of employees’ opinions. Results from the one-to-one interviews highlight an increased need for communication, feedback and support. These issues are also apparent in the 2011 DHL Employee Opinion Survey results. The interviews emphasised positive attitudes towards the company, but less so, in some cases, towards management. Interview findings and DHL opinion survey results positively connect EE to sufficient compensation and good working conditions; organisational and supervisor support; organisational commitment; good subordinate-manager relationships and frequent subordinate-manager communication and reduced turnover. Research limitations/ implications – Additional research is needed to assess the ‘generalisability’ of the findings, and to further investigate the impact of age, gender and time served upon engagement levels. Keywords Employee engagement, Employee involvement, Employee attitudes, Feedback, Job satisfaction Paper type Case study